2019
DOI: 10.1002/met.1773
|View full text |Cite
|
Sign up to set email alerts
|

Objective identification of Mediterranean cyclones and their trajectories towards Romania

Abstract: A mathematical algorithm for the automatic detection and tracking of Mediterranean cyclones is presented. The objective of this study is identifying those Mediterranean cyclones that are engaged on various trajectories towards the countries bordering the Black Sea. Mediterranean cyclones with trajectories towards Romania have been identified from a six‐hourly reanalysis of mean sea level pressure (MSLP) data set for a period of 37 years (January 1980–December 2016) within the chosen domain 15 ° W–40 ° E/30 ° N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 93 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…For the extra tropics, the MSLP or the geostrophic vorticity fields were most often used for these types of studies [52,53]. In addition, for this study the algorithm was verified for the nine main clusters that were found to be representative for the climatology over the target domain [10], by simulating the central cluster event and analyzing the origin, development, and larger-scale context for each (presented in Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the extra tropics, the MSLP or the geostrophic vorticity fields were most often used for these types of studies [52,53]. In addition, for this study the algorithm was verified for the nine main clusters that were found to be representative for the climatology over the target domain [10], by simulating the central cluster event and analyzing the origin, development, and larger-scale context for each (presented in Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…The following are available online at https://www.mdpi.com/article/ 10.3390/atmos12101362/s1, Figure S1: Validation of storm track classes from Catrina et al, 2019. Computed trajectories are blue/ red lines for winter/ summer events; plum cross represents the track position from meteorological analysis in (Catrina et al, 2019); orange circle represents secondary cyclonic forcing position present in the same time, interacting with the track, but not identified as cyclone center; orange dot lines indicate larger-scale context previous or during to the track (lead time is written in orange, in hours). Figure S2: Represents the same as in Figure 11 for average months SON.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two primary methods for classifying synoptic patterns [63,64]. The first is subjective classification, and the second involves using objective methods, such as correlation analysis, cluster analysis, nonlinear techniques, neural networks, and more [64,65], all used to identify consistent weather patterns [66]. Hierarchical clustering methods are well-suited for the exploratory phase of research [67], with Ward's method [68] being one of the main hierarchical clustering techniques in climatic classifications that has been employed in various studies [66,67,69,70].…”
mentioning
confidence: 99%